Lesiones en windsurfistas de elite masculinos - Perez-Turpin, J. A.; Cortell-Tormo, J. M.; Suarez-Llorca, C; Chinchilla-Mira, J. J.; Cejuela-Anta, R.; Andreu-Cabrera, E. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2012)
The aim of this study was to determine the percentage of injuries and body parts sport in male pro riders. We performed a descriptive epidemiological study. Were collected using a specifically designed questionnaire and retrospective elite windsurfers to 39, participating in the World Cup finals in Fuerteventura (2008). The 84.6% of injuries occurred in the lower extremities (61.5%, p <0.01 knee, leg 15.4%, 5.1% and 2.6% ankle foot). 10.3% occurred in the back and 5.1% in the head. These injuries occurred during competition more (79.5%, P <0.01) than in training. These results indicate the need for new methods of prevention for the lower body, especially in the form of slalom and knee and the use of materials to protect the head during the competition.